O Bumba-meu-boi de Matraca: Uma abordagem geográfica sobre o Festejo de São Marçal no Bairro do João Paulo em São Luís - MA - CASTRO, Wallace Nogueira (2023)
This grandiose demonstration currently takes place every June 30th in the João Paulo neighborhood in São Luís do Maranhão. It was built slowly from 1928, when local traders took the first groups there. At that time, there was no adequate structure to receive the celebration in the size of what it is today, AV. São Marçal was part of the so-called Caminho Grande. In relation to the saint who gives the name to the festivities, São Marçal is considered the patron saint of firefighters, and of the cattlemen of Maranhão, due to this fact, it is only fair that he is honored by the groups of Bumba-meu-boi. The festivities present cultural traits in which the people maintain their identity through the bumba-boi groups of the matraca accent and religiosity. There is a mixture in the space between the sacred and the profane. This interaction is classified as follows: the interdependencies and functional relationships between the sacred space and the profane space, which take place in sacred times, allow characterizing the profane space and suggesting a classification in relation to its greater or lesser link with the sacred. Based on these assumptions, the present work aims to analyze the socio-spatial dynamics produced by the Festa de São Marçal, from the main groups of Bumba-meu-boi and the pranksters, highlighting the cultural manifestation as a phenomenon of iron and struggle and producer of inter -sociocultural relations between the participants. For the construction of the work, a search and collection of historical data was carried out through the survey and analysis of the existing bibliographic material on the subject object of study, available in books, theses, dissertations, academic works and on the various internet sites that published material related to the subject theme. The "in loco" perception consists of an empirical analysis of the area of the João Paulo neighborhood, specifically Avenida São Marçal, together with the coordinators of chosen groups that most impact the party, which are: Bumba-Meu-Boi do João Paulo, do Bairro de Fátima, Maioba and Maracanã, with interviews with their players, coordinators, and also dialogue with the residents and merchants of the João Paulo neighborhood. These steps aim to understand the social integration exercised in the neighborhood before, during and after the event, under a methodological bias of a qualitative nature, in this case study. The result of the entire investigation will provide answers through samples, on demographic, educational and economic variables, on the players of the Bumba-meu-boi groups, the social and integrative role of the groups, and on the main influences of the sectors directly related to the event. such as commercial enterprises, informal traders, and residents located in the neighborhood.